Breastfeeding may provide on-the-job training of self-regulation: Longitudinal links with inhibitory control - Sophie Jacques; Sophie Parent; Natalie Castellanos-Ryan; Jean R. Séguin; Philip David Zelazo (Appetite, 2026)

Retraction notice to “Chemical weathering and CO2 consumption in the upper Nyong Basin rivers (Central Africa): Insights on climatic and anthropogenic forcing in humid tropical environments” [Sci. Total Environ. 937 (2024) 173405] - David Eric Komba; Bertil Nlend; Jean Jacques Braun; Suzanne Ngo Boum-Nkot; Stéphane Audry; Gustave Raoul Nkoue Ndondo; Jean Riotte; Bernadette Nka Nnomo; Marie Joseph Ntamak-Nida; Jacques Etame; Enoh Jeanot Fongoh; Henriette Ateba Bessa; et al. (Science of The Total Environment, 2026)

Hop leaf phenolics as a source of natural antioxidants - Duncan Calvert; Tristan Dew; Arthur Gadon; Jacques Gros; David Cook (Food Chemistry, 2026)

Assessment of heavy metal contamination and its ecological risks in the surface sediments along the lower part of the Cameroonian coast - Arcange Duviol Tsanga; Armel Zacharie Ekoa Bessa; Durane Chougong Tchatchouang; Same Moutongo Jacques-David; Gerardine Saurelle Ngokam; Dairou Bachirou; Eugenie Kenne; Gabriel Ngueutchoua (Arabian Journal of Geosciences, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Impact of acute sleep restriction on resting ventilation and cytokine levels in normobaric hypoxia, and their association - Louis David; Julianne Touron; Marie-Claire Erkel; Catherine Drogou; Anaïs Pontiggia; Vincent Beauchamps; Carine Malle; Olivier Nespoulous; Ulysse Comte; Alexandra Malgoyre; Fabien Sauvet; Beth A. Beidleman; et al. (European Journal of Applied Physiology, 2026)

Palynological pairing of archaeological rock shelter and swamp deposits on the Arnhem Plateau: Holocene ecological changes at Nawarla Gabarnmang and Swamp 7, Northern Territory - Cassandra Rowe; Janelle Stevenson; Bruno David; Jean-Jacques Delannoy; Ulrike Proske (Vegetation History and Archaeobotany, 2026)

Advancing provitamin A biofortification in sorghum: from allele mining and marker development to prebreeding and breeding - Clara Cruet-Burgos; Linly Banda; Jacques M. Faye; Cyril Diatta; David Zapata; Geoffrey P. Morris; Davina H. Rhodes (Theoretical and Applied Genetics, 2026)
Key message Allele mining for provitamin A biofortification in sorghum is advanced with new pre-bred germplasm and markers that are trait-predictive in diverse germplasm and breeding programs. Abstract Provitamin A biofortification of the staple cereal crop sorghum ( Sorghum bicolor [L.] Moench) could reduce vitamin A deficiency in low-income countries of sub-Saharan Africa. To advance mining of alleles that confer high provitamin A from genebank accessions, we developed prebreeding germplasm and trait-predictive markers, and established the utility of these markers in a range of prebreeding and breeding materials. We first tested the hypothesis that carotenoid concentrations in sorghum grain can be increased through breeding using six biparental families developed from high-carotenoid genebank accessions. The families exhibited abundant transgressive segregation for carotenoid concentrations, with positive asymmetry in many cases (4 of 6 families) suggesting the release of epistatic variation. Next, we developed eleven markers from SNPs associated with carotenoid variation, and validated their predictiveness in the six biparental families and diverse global germplasm. Two markers (snpSB00267 and snpSB00276), previously identified as zeaxanthin QTLs, were predictive of provitamin A content (β-carotene) in the biparental family evaluated and the diverse germplasm, and require further validation. Five markers that were predictive of zeaxanthin content—most notably snpSB00265, located within the zeaxanthin epoxidase ( ZEP ) gene; snpSB00277 and snpSB00264, near ZEP ; and snpSB00279 and snpSB00280, in the β-carotene 3-hydroxylase gene—are recommended for indirect selection for provitamin A carotenoids. In a Senegalese breeding program, most markers (9 of 11) were segregating and contrasted for the elite germplasm (low carotenoid alleles) and yellow-endosperm donor lines (high carotenoid). Together, findings show that sorghum grain carotenoids can be increased through breeding, and demonstrate the potential of marker-assisted selection for provitamin A biofortification.

Open Questions on Ion–Neutral Collisions and Coupling in the Lower Thermosphere–Ionosphere: Electrodynamics, Energetics and Dynamics - Theodoros E. Sarris; Stelios Tourgaidis; Dimitrios Baloukidis; Maxime Grandin; Astrid Maute; Robert F. Pfaff; Jeffrey Thayer; James Clemmons; Karl Laundal; Hanli Liu; Panagiotis Pirnaris; Noora Partamies; et al. (Surveys in Geophysics, 2026)
The Lower Thermosphere–Ionosphere (LTI) is the interface region between the Earth’s atmosphere and space. It is modulated by the energy and momentum deposition from the magnetosphere above and by the impacting waves from the lower atmosphere. The LTI region is defined by the co-existence and interaction of neutral and ionized species within the region’s electric and magnetic fields. This interplay results in unique and complex interactions between neutrals and plasmas, that are not fully understood and quantified to this date. In this paper we present an overview of some of the most important open questions related to ion/neutral coupling and the resulting collisional electrodynamics, collisional energetics and collisional dynamics processes. We outline the key reasons for addressing these questions, and highlight methodologies that can lead to their closure in the upcoming years.

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The First France-Armenia Hematology Day: Medicine in the Service of Peace, Science and Bone Marrow Transplantation - Jacques-Oliver Bay; Christian Chabannon; Patrice Ceballos; Gandhi Damaj; Gérard Hovakimian; Mohamed Mohty; Philippe Moreau; Florian Scotté; David M. Smadja; Ibrahim Yakoub-Agha (Stem Cell Reviews and Reports, 2026)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Phenotypic diversity of Saharan wheat landraces growing on oasis farms in Algeria: the influence of climate and geography on the distribution of traits - Sabrina Oumata; Philippe Monneveux; Maria Zaharieva; Samia Yahiaoui; Leila Mekliche-Hanifi; Jacques David (Genetic Resources and Crop Evolution, 2025)

Seed management and selection in ancient maize landraces from the French Pyrenees: ethnobotanical survey and selection experiment - Brigitte Gouesnard; Yacine Diaw; Laurène Gay; Joëlle Ronfort; Jacques David (Genetic Resources and Crop Evolution, 2025)
Maize landraces ( Zea mays subsp. mays ) have evolved under the joint action of environmental factors and of the farmers who cultivated them. In this study, we aim to quantify the selection gradients exerted by farmers by proposing them a selection test consisting in choosing the ears they would select if they were to grow maize landraces the following year. The study focused on the Pyrenees region of France, where landraces were cultivated until the arrival of hybrids in the 1960s and conserved ex-situ ever since. We interviewed former Pyrenean farmers or their children who were cultivating landraces 60 years ago. The survey documented seed management practices and know-how. Our selection test showed that their selection was based solely on ears: old farmers selected healthy and productive ears by using ear length and volume as the first two selection criteria. Both were highly correlated with the kernel weight per ear. Heritabilities of ear traits at an individual plant level were estimated in one trial for four landraces and were found variable between traits and landraces (average 0.36 ranging between 0 and 0.76). We calculated the expected genetic change after one generation of mass selection, following farmer selection criteria. For ear length, genetic change was expected to reach about 3.4% (from 1 to 7.5% over the 17 selection tests). We investigated seed selection practices both east and west of the Pyrenees and compared them qualitatively with those of native American farmers.

The impact of sea level rise on nesting sea turtles: a global meta-analysis to highlight current understanding and knowledge gaps - Melissa N. Staines; David T. Booth; Jacques-Olivier Laloë; Graeme C. Hays (Marine Biology, 2025)
Sea turtles face a number of threats from climate change. One pertinent threat is the impact of sea level rise (SLR), which can lead to a loss of nesting habitat and reduced survival of embryos due to inundation and erosion. Here we review the impacts of SLR on sea turtles. We examined 34 studies (66 assessments) on SLR impacts across six species and 40 sites globally, with 62.1% of assessments located in the Americas. Overall, 78.8% of the assessments showed declining trends in historical and projected estimates of nesting habitat area and or nest survival from inundation. Assessments with projected nesting habitat area showed appreciable loss across all site types (coral island, elevated island, barrier island and mainland), regardless of the SLR scenario. The projected percentage of habitat loss and nest flooding was greatest in island sites compared to the mainland sites, highlighting that SLR is likely to be most acute for low-lying islands with no nearby alternative nesting areas. We reviewed the predicted extent of nesting beach loss and examined how natural processes and conservation interventions might mitigate this threat. However, we require more empirical data on the extent of historical nesting habitat loss. There is also little known about a population’s ability to colonise new nesting areas once a site becomes unsuitable. By tracking their routes towards the breeding sites, there is potential to show how resilient sea turtles are to environmental change, as females may be exposed to other suitable nesting sites on their migration route.

Mesophotic protected habitats as refugia for the most at-risk elasmobranch species - Franck Pichot; Stéphanie Manel; Laure Velez; Jean-Baptiste Juhel; Laurent Ballesta; Pierre Boissery; Morgane Bruno; Maddy Cancemi; Florian Holon; Jean-Jacques Riutort; Marieke Schultz; Nicolas Tomasi; et al. (Biological Conservation, 2025)

The Impact of Postprocedural Anticoagulant Use in Patients Undergoing Woven EndoBridge: A Multicenter Propensity Score-Matched Study - Basel Musmar; Hamza Adel Salim; Joanna M. Roy; Nimer Adeeb; Antony A. Fuleihan; Elias Atallah; Saman Sizdahkhani; Sravanthi Koduri; Spyridon Karadimas; Bachar El Baba; Brian M. Howard; Jonathan A. Grossberg; et al. (Translational Stroke Research, 2025)

Tensions in tillage: Reduction in tillage intensity associates with lower wheat growth and nutritional grain quality despite enhanced soil biological indicators - Matthias Waibel; Jennifer Michel; Maurine Antoine; Iñaki Balanzategui-Guijarro; Da Cao; Pierre Delaplace; Jacques Le Gouis; David Alvarez; Claire Léon; Sandy Manfroy; Jordi Moya-Laraño; Sibille Perrochon; et al. (Agriculture, Ecosystems & Environment, 2025)

Enhancing the Nektar++ spectral/hp element framework for parallel-in-time simulations - Jacques Y. Xing; Chris D. Cantwell; David Moxey (Computer Physics Communications, 2025)

Global Decline in the Size of Sea Turtles - Graeme C. Hays; Mohd Uzair Rusli; David Booth; Jacques‐Olivier Laloë (Global Change Biology, 2025)
Changes in mean adult body size may be a universal response to global warming and sometimes lead to conservation concerns. We show that size reductions in sea turtles are now the norm and have another explanation. From 18,707 measurements of nester size (curve carapace length) for sea turtles spanning 30 years from Redang Island (Malaysia), where nearly all nesting individuals have been tagged, we show that the mean size was initially fairly stable and then decreased by 4.0 cm from 100.8 cm in 2005 to 96.8 cm in 2022, which likely translates to a change in mean mass from 120 to 105 kg. At the same time, nesting increased from around 300 to 2000 nests per year. Consistent with this finding of a size reduction in an expanding population, at 27 of 31 sites across the globe where changes in the mean size of nesting sea turtles have been assessed, mean size is decreasing, and the most marked decreases are at sites where population size is increasing most dramatically. Taken together, these focal and global findings suggest that an important driver of size reductions in sea turtles is an influx of small first‐time nesters (neophytes) in expanding populations, and hence, size reductions are partially a consequence of successful sea turtle conservation measures and population recoveries. At the same time, the focal observations in Malaysia show that the mean size of neophytes has also been getting smaller over time: from 99.6 to 96.8 cm between 2005 and 2022, likely because of a change in foraging environments. While smaller turtles have lower reproductive output, this negative consequence of decreases in nester size will often be more than offset by increases in nesting numbers that are occurring widely.

Central-venous-catheter-related bloodstream infections in adult patients with sickle cell disease: a retrospective, two-centre study - Matthieu Holub; David Lebeaux; Patrick Grohs; Laure Joseph; Olivier Pellerin; Geoffrey Cheminet; Najiby Kassis; Salomé Abdellaoui; Jacques Pouchot; Brigitte Ranque; Jean Benoit Arlet; Emmanuel Lafont (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Les empreintes de dinosaures du Jurassique inférieur de Peyre (Aveyron, France) : fouille récente et nouvelles données ichnologiques révélées par imagerie 3D - Jean-David Moreau; Jacques Sciau; Ethan Jean (Annales de Paléontologie, 2025)

Three‐dimensional conservation planning of fish biodiversity metrics to achieve the deep‐sea 30×30 conservation target - Laetitia Mathon; Florian Baletaud; Anne Lebourges‐Dhaussy; Gaël Lecellier; Christophe Menkes; Céline Bachelier; Claire Bonneville; Tony Dejean; Mahé Dumas; Sylvie Fiat; Jacques Grelet; Jérémie Habasque; et al. (Conservation Biology, 2025)
Accelerating rate of human impact and environmental change severely affects marine biodiversity and increases the urgency to implement the Convention on Biological Diversity (CBD) 30×30 plan for conserving 30% of sea areas by 2030. However, area‐based conservation targets are complex to identify in a 3‐dimensional (3D) ocean where deep‐sea features such as seamounts have been seldom studied mostly due to challenging methodologies to implement at great depths. Yet, the use of emerging technologies, such as environmental DNA combined with modern modeling frameworks, could help address the problem. We collected environmental DNA, echosounder acoustic, and video data at 15 seamounts and deep island slopes across the Coral Sea. We modeled 7 fish community metrics and the abundances of 45 individual species and molecular operational taxonomic units (MOTUs) in benthic and pelagic waters (down to 600‐m deep) with boosted regression trees and generalized joint attribute models to describe biodiversity on seamounts and deep slopes and identify 3D protection solutions for achieving the CBD area target in New Caledonia (1.4 million km 2 ). We prioritized the identified conservation units in a 3D space, based on various biodiversity targets, to meet the goal of protecting at least 30% of the spatial domain, with a focus on areas with high biodiversity. The relationship between biodiversity protection targets and the spatial area protected by the solution was linear. The scenario protecting 30% of each biodiversity metric preserved almost 30% of the considered spatial domain and accounted for the 3D distribution of biodiversity. Our study paves the way for the use of combined data collection methodologies to improve biodiversity estimates in 3D structured marine environments for the selection of conservation areas and for the use of biodiversity targets to achieve area‐based international targets.

Valorisation of hop leaves for their bioactive compounds: Identification and quantification of phenolics across different varieties, crop years and stages of development. - Duncan Calvert; Tristan Dew; Arthur Gadon; Jacques Gros; David Cook (Food Chemistry, 2025)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Synthesis and quantification of oligoesters migrating from starch-based food packaging materials - David Rupérez; Matthieu Rivière; Jacques Lebreton; Margarita Aznar; Filomena Silva; Arnaud Tessier; Ronan Cariou; Cristina Nerín (Journal of Hazardous Materials, 2024)

RETRACTED: Chemical weathering and CO2 consumption in the upper Nyong Basin rivers (Central Africa): Insights on climatic and anthropogenic forcing in humid tropical environments - David Eric Komba; Bertil Nlend; Jean Jacques Braun; Suzanne Ngo Boum-Nkot; Stéphane Audry; Gustave Raoul Nkoue Ndondo; Jean Riotte; Bernadette Nka Nnomo; Marie Joseph Ntamak-Nida; Jacques Etame; Enoh Jeanot Fongoh; Henriette Ateba Bessa; et al. (Science of The Total Environment, 2024)

Ant rarity and vulnerability in Brazilian Atlantic Forest fragments - Nathalia S. Silva; Everton A. Maciel; Lívia P. Prado; Otávio G.M. Silva; David Aciole Barbosa; Joudellys Andrade-Silva; Débora R. Souza-Campana; Rogério R. Silva; Carlos R.F. Brandão; Jacques H.C. Delabie; Maria S.C. Morini (Biological Conservation, 2024)

Novel Superadsorbent from Pozzolan-Charcoal based Geopolymer Composite for the Efficient Removal of Aqueous Crystal Violet - Jacques Madiba Mboka; Hermann Dzoujo Tamaguelon; Victor Shikuku; Sylvain Tome; Valery Franck Deugueu; Hanibal Othman; Christoph Janiak; Marchand Manga Dika; Marie Annie Etoh; David Joh Daniel Dina (Water, Air, & Soil Pollution, 2024)

Wheat dwarfing reshapes plant and fungal development in arbuscular mycorrhizal symbiosis - Pierre-Louis Alaux; Pierre-Emmanuel Courty; Hélène Fréville; Jacques David; Aline Rocher; Elisa Taschen (Mycorrhiza, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Depth of the lithospheric mantle discontinuities beneath the northwest flank of Oku Volcanic Complex, Cameroon Volcanic Line: constraints from mantle xenolith and teleseismic data - Marie-Louise Vohnyui Chenyi; Pierre Wotchoko; Jacques-Marie Bardintzeff; Adoua Kopa Njueya; David Guimolaire Nkouathio (Arabian Journal of Geosciences, 2024)

Groundwater quality status in the Division of Fitri (Chad) - Atteib Adam Baye; Suzanne Ngo Boum-Nkot; Mohammad Bello; Bertil Nlend; Boris Djieugoue; Fricelle Song; David Komba; Djibrine Adoum Oumar; Jacques Etame (Sustainable Water Resources Management, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

[18F]-FDopa positron emission tomography imaging in corticobasal syndrome - Anaïs El Ouartassi; Caroline Giordana; Aurélie Schiazza; David Chardin; Jacques Darcourt (Brain Imaging and Behavior, 2023)

Short‐term resilience to climate‐induced temperature increases for equatorial sea turtle populations - Melissa N. Staines; Hayley Versace; Jacques‐Olivier Laloë; Caitlin E. Smith; Christine A. Madden Hof; David T. Booth; Ian R. Tibbetts; Graeme C. Hays (Global Change Biology, 2023)
Projection models are being increasingly used to manage threatened taxa by estimating their responses to climate change. Sea turtles are particularly susceptible to climate change as they have temperature‐dependent sex determination and increased sand temperatures on nesting beaches could result in the ‘feminisation’ of hatchling sex ratios for some populations. This study modelled likely long‐term trends in sand temperatures and hatchling sex ratios at an equatorial nesting site for endangered green turtles ( Chelonia mydas ) and critically endangered hawksbill turtles ( Eretmochelys imbricata ). A total of 1078 days of sand temperature data were collected from 28 logger deployments at nest depth between 2018 and 2022 in Papua New Guinea (PNG). Long‐term trends in sand temperature were generated from a model using air temperature as an environmental proxy. The influence of rainfall and seasonal variation on sand temperature was also investigated. Between 1960 and 2019, we estimated that sand temperature increased by ~0.6°C and the average hatchling sex ratio was relatively balanced (46.2% female, SD = 10.7). No trends were observed in historical rainfall anomalies and projections indicated no further changes to rainfall until 2100. Therefore, the sex ratio models were unlikely to be influenced by changing rainfall patterns. A relatively balanced sex ratio such as this is starkly different to the extremely female‐skewed hatchling sex ratio (>99% female) reported for another Coral Sea nesting site, Raine Island (~850 km West). This PNG nesting site is likely rare in the global context, as it is less threatened by climate‐induced feminisation. Although there is no current need for ‘cooling’ interventions, the mean projected sex ratios for 2020–2100 were estimated 76%–87% female, so future interventions may be required to increase male production. Our use of long‐term sand temperature and rainfall trends has advanced our understanding of climate change impacts on sea turtles.

Earth's rotation and Earth-Moon distance in the Devonian derived from multiple geological records - Christian Zeeden; Jacques Laskar; David De Vleeschouwer; Damien Pas; Anne-Christine Da Silva (Earth and Planetary Science Letters, 2023)

Highly energetic rockfalls: back analysis of the 2015 event from the Mel de la Niva, Switzerland - François Noël; Synnøve Flugekvam Nordang; Michel Jaboyedoff; Julien Travelletti; Battista Matasci; Michaël Digout; Marc-Henri Derron; Andrin Caviezel; Clément Hibert; David Toe; Miloud Talib; Emmanuel Wyser; et al. (Landslides, 2023)
Process-based rockfall simulation models attempt to better emulate rockfall dynamics to different degrees. As no model is perfect, their development is often accompanied and validated by the valuable collection of rockfall databases covering a range of site geometries, rock masses, velocities, and related energies that the models are designed for. Additionally, such rockfall data can serve as a base for assessing the model’s sensitivity to different parameters, evaluating their predictability and helping calibrate the model’s parameters from back calculation and analyses. As the involved rock volumes/masses increase, the complexity of conducting field-test experiments to build up rockfall databases increases to a point where such experiments become impracticable. To the author’s knowledge, none have reconstructed rockfall data in 3D from real events involving block fragments of approximately 500 metric tons. A back analysis of the 2015 Mel de la Niva rockfall event is performed in this paper, contributing to a novel documentation in terms of kinetic energy values, bounce heights, velocities, and 3D lateral deviations of these rare events involving block fragments of approximately 200 m 3 . Rockfall simulations are then performed on a “per-impact” basis to illustrate how the reconstructed data from the site can be used to validate results from simulation models.

Verification and benchmarking relativistic electron beam transport through a background gas - Brandon M. Medina; Pierre Grua; Keith L. Cartwright; David Hébert; Nicolas Szalek; Clément Caizergues; Israel Owens; Elaine L. Rhoades; Jacques Gardelle; Christopher H. Moore (Computer Physics Communications, 2023)

Best practices in the use and exchange of microorganism biological control genetic resources - Peter G. Mason; Martin Hill; David Smith; Luciana C. Silvestri; Philip Weyl; Jacques Brodeur; Marcello Diniz Vitorino (BioControl, 2023)
The Nagoya Protocol actions the third objective of the Convention on Biological Diversity and provides a framework to effectively implement the fair and equitable sharing of benefits arising out of the use of genetic resources. This includes microorganisms used as biological control agents. Thus biological control practitioners must comply with access and benefit-sharing regulations that are implemented by countries providing microbial biological control agents. A review of best practices and guidance for the use and exchange of microorganisms used for biological control has been prepared by the IOBC Global Commission on Biological Control and Access and Benefit-Sharing to demonstrate commitment to comply with access and benefit-sharing requirements, and to reassure the international community that biological control is a very successful and environmentally safe pest management strategy that uses biological resources responsibly and sustainably. We propose that best practices include the following elements: collaboration to facilitate information exchange about the availability of microbial biological control agents and where they may be sourced; freely sharing available knowledge in databases about successes and failures; collaborative research with provider countries to develop capacity; and production technology transfer to provide economic opportunities. We recommend the use of model concept agreements for accessing microorganisms for scientific research and non-commercial release into nature where access and benefit-sharing regulations exist and where regulations are not restrictive or do not exist. We also recommend a model agreement for deposition of microbial biological control agents into culture collections.

Main drivers of marine heat waves in the eastern South Pacific - David Carrasco; Oscar Pizarro; Martín Jacques-Coper; Diego A. Narváez (Frontiers in Marine Science, 2023)
During the last decades, marine heat waves (MHWs) have increased in frequency and duration, with important impacts on marine ecosystems. This trend has been related to rising global sea surface temperatures, which are expected to continue in the future. Here, we analyze the main characteristics and possible drivers of MHWs in the eastern South Pacific off Chile. Our results show that MHWs usually exhibit spatial extensions on the order of 10 3 -10 4 km 2 , temperature anomalies in the mixing layer between 1 and 1.3°C, and durations of 10 to 40 days, with exceptional events lasting several months. In this region, MHW are closely related to the ENSO cycles, in such a way that El Niño and, to a lesser extent, La Niña events increase the probability of high intensity and extreme duration MHWs. To analyze the MHW drivers, we use the global ocean reanalysis GLORYS2 to perform a heat budget in the surface mixed layer. We find that most events are dominated by diminished heat loss –associated with reduced evaporation– and enhanced insolation; thus, this group is called ASHF (for air-sea heat fluxes). The second type of MHWs is driven by heat advection, predominantly forced by anomalous eastward surface currents superimposed on a mean westward temperature gradient. The third type of MHWs results from a combination of positive (seaward) anomalies of air-sea heat fluxes and heat advection; this group exhibits the greatest values of spatial extension, intensity, and duration.

Evaluation of provenance and weathering of beach sediments in the lower part of the Cameroonian coast - Arcange Duviol Tsanga; Armel Zacharie Ekoa Bessa; Gabriel Ngueutchoua; Gerardine Saurelle Ngokam; Same Moutongo Jacques-David; Victorine Ambassa Bela; Annick Kwewouo Janpou; Mohamed Abioui; John S. Armstrong-Altrin (Journal of African Earth Sciences, 2023)

Variation of morphological traits among wheat (Triticum aestivum L.) landraces from two regions of the Algerian Sahara. Potential interest for wheat breeding - Sabrina Oumata; Philippe Monneveux; Maria Zaharieva; Leila Mekliche-Hanifi; Jacques David (Genetic Resources and Crop Evolution, 2023)

Toward a common approach for assessing the conservation status of marine turtle species within the european marine strategy framework directive - Fanny Girard; Alexandre Girard; Jonathan Monsinjon; Antonella Arcangeli; Eduardo Belda; Luis Cardona; Paolo Casale; Sidonie Catteau; Léa David; Florence Dell’Amico; Delphine Gambaiani; Marc Girondot; et al. (Frontiers in Marine Science, 2022)
Environmental policies, including the European Marine Strategy Framework Directive (MSFD), generally rely on the measurement of indicators to assess the good environmental status (GES) and ensure the protection of marine ecosystems. However, depending on available scientific knowledge and monitoring programs in place, quantitative GES assessments are not always feasible. This is specifically the case for marine turtle species, which are listed under the Biodiversity Descriptor of the MSFD. Relying on an expert consultation, the goal of this study was to develop indicators and a common assessment approach to be employed by European Union Member States to evaluate the status of marine turtle populations in the frame of the MSFD. A dedicated international expert group was created to explore and test potential assessment approaches, in coherence with other environmental policies (i.e. Habitats Directive, OSPAR and Barcelona Conventions). Following a series of workshops, the group provided recommendations for the GES assessment of marine turtles. In particular, indicators and assessment methods were defined, setting a solid basis for future MSFD assessments. Although knowledge gaps remain, data requirements identified in this study will guide future data collection initiatives and inform monitoring programs implemented by EU Member States. Overall this study highlights the value of international collaboration for the conservation of vulnerable species, such as marine turtles.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Insights into HIV uncoating from single-particle imaging techniques - Margaret J. Zhang; Jeffrey H. Stear; David A. Jacques; Till Böcking (Biophysical Reviews, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

The last 750 ka in loess–palaeosol sequences from northern France: environmental background and dating of the western European Palaeolithic - Pierre Antoine; Sylvie Coutard; Jean‐Jacques Bahain; Jean‐Luc Locht; David Hérisson; Emilie Goval (Journal of Quaternary Science, 2021)
This study presents an overview of Middle Pleistocene loess–palaeosol sequences (LPS) in northern France and discusses the palaeoclimatic significance of the pedosedimentary record in the context of western European LPS and of global climatic cycles for the last 750 ka. In this area, the oldest loess deposits (early Middle Pleistocene) are preserved in sedimentary traps (leeward scarps of fluvial terraces and dissolution sinkholes). They result from local deflation processes reworking Pleistocene sandy fluvial deposits or relicts of Tertiary sands. A large extension of typical calcareous loess over the landscape, the Loess Revolution , is then observed during MIS 6, with heavy mineral assemblages testifying to long‐distance transport from the polar desert area of the dried eastern Channel. A correlation scheme is proposed between the global records of northern France in continental environments and both global palaeoclimatic records and other main western European LPS. After 30 years of research, northern France LPS stand as a fundamental archive of the impact of interglacial–glacial climatic cycles as well as millennial events. Finally, these works provide a robust chronoclimatic framework for the study of the western European Late Acheulean and Middle Palaeolithic and for the relative dating of the various fluvial terraces that they fossilise.

The role of testosterone replacement therapy and statin use, and their combination, in prostate cancer - David S. Lopez; Danmeng Huang; Konstantinos K. Tsilidis; Steven Canfield; Mohit Khera; Jacques G. Baillargeon; Yong-Fang Kuo; M. Kristen Peek; Elizabeth A. Platz; Kyriakos Markides (Cancer Causes & Control, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Prioritizing the provision of urban ecosystem services in deprived areas, a question of environmental justice - Wissal Selmi; Slaheddine Selmi; Jacques Teller; Christiane Weber; Emmanuel Rivière; David J. Nowak (Ambio, 2021)

Prevalence of hyposmia and hypogeusia in 390 COVID-19 hospitalized patients and outpatients: a cross-sectional study - Agathe Nouchi; Julie Chastang; Makoto Miyara; Julie Lejeune; André Soares; Gladys Ibanez; David Saadoun; Capucine Morélot-Panzini; Thomas Similowski; Zahir Amoura; Jacques Boddaert; Eric Caumes; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Density‐dependent natural selection mediates harvest‐induced trait changes - Alix Bouffet‐Halle; Jacques Mériguet; David Carmignac; Simon Agostini; Alexis Millot; Samuel Perret; Eric Motard; Beatriz Decenciere; Eric Edeline (Ecology Letters, 2021)
Rapid life‐history changes caused by size‐selective harvesting are often interpreted as a response to direct harvest selection against a large body size. However, similar trait changes may result from a harvest‐induced relaxation of natural selection for a large body size via density‐dependent selection. Here, we show evidence of such density‐dependent selection favouring large‐bodied individuals at high population densities, in replicated pond populations of medaka fish. Harvesting, in contrast, selected medaka directly against a large body size and, in parallel, decreased medaka population densities. Five years of harvesting were enough for harvested and unharvested medaka populations to inherit the classically predicted trait differences, whereby harvested medaka grew slower and matured earlier than unharvested medaka. We show that this life‐history divergence was not driven by direct harvest selection for a smaller body size in harvested populations, but by density‐dependent natural selection for a larger body size in unharvested populations.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

Influenza-associated aspergillosis in critically-ill patients—a retrospective bicentric cohort study - Frederike Waldeck; Filippo Boroli; Noémie Suh; Pedro David Wendel Garcia; Domenica Flury; Julia Notter; Anne Iten; Laurent Kaiser; Jacques Schrenzel; Katia Boggian; Marco Maggiorini; Jérôme Pugin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Implementation of the WASPLab™ and first year achievements within a university hospital - Abdessalam Cherkaoui; Gesuele Renzi; Arnaud Viollet; Mark Fleischmann; Ludovic Metral-Boffod; David Dominguez-Amado; Nicolas Vuilleumier; Jacques Schrenzel (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Genome wide association mapping for resistance to multiple fungal pathogens in a panel issued from a broad composite cross-population of tetraploid wheat Triticum turgidum - Elsa Ballini; Muriel Tavaud; Aurélie Ducasse; Dimitri Sanchez; Etienne Paux; Jonathan Kitt; Gilles Charmet; Delphine Audigeos; Pierre Roumet; Jacques David; Jean-Benoit Morel (Euphytica, 2020)

Oasis wheats of the South of Algeria: landraces, cultural practices and utilization - Sabrina Oumata; Jacques David; Leila Mekliche-Hanifi; Mohamed Kharsi; Maria Zaharieva; Philippe Monneveux (Genetic Resources and Crop Evolution, 2020)

First in situ pXRF analyses of rock paintings in Erongo, Namibia: results, current limits, and prospects - Guilhem Mauran; Matthieu Lebon; Florent Détroit; Benoît Caron; Alma Nankela; David Pleurdeau; Jean-Jacques Bahain (Archaeological and Anthropological Sciences, 2019)

NF1 Somatic Mutation in Dystrophic Scoliosis - Rebecca L. Margraf; Chad VanSant-Webb; Rong Mao; David H. Viskochil; John Carey; Heather Hanson; Jacques D’Astous; Allie Grossmann; David A. Stevenson (Journal of Molecular Neuroscience, 2019)

A response to “Personalised medicine and population health: breast and ovarian cancer” - Antonis Antoniou; Hoda Anton-Culver; Alexander Borowsky; Mireille Broeders; Jennifer Brooks; Anna Chiarelli; Jocelyne Chiquette; Jack Cuzick; Suzette Delaloge; Peter Devilee; Michael Dorval; Douglas Easton; et al. (Human Genetics, 2019)

Algorithmic Complexity of EEG for Prognosis of Neurodegeneration in Idiopathic Rapid Eye Movement Behavior Disorder (RBD) - Giulio Ruffini; David Ibañez; Eleni Kroupi; Jean-François Gagnon; Jacques Montplaisir; Ronald B. Postuma; Marta Castellano; Aureli Soria-Frisch (Annals of Biomedical Engineering, 2019)

Teleconnection stationarity, variability and trends of the Southern Annular Mode (SAM) during the last millennium - Christoph Dätwyler; Raphael Neukom; Nerilie J. Abram; Ailie J. E. Gallant; Martin Grosjean; Martín Jacques-Coper; David J. Karoly; Ricardo Villalba (Climate Dynamics, 2018)

Do natural enemies explain fluctuations in low‐density spruce budworm populations? - Mathieu Bouchard; Véronique Martel; Jacques Régnière; Pierre Therrien; David Laginha Pinto Correia (Ecology, 2018)
Understanding the causal pathways through which forest insect outbreaks are triggered is important for resource managers. However, detailed population dynamics studies are hard to conduct in low‐density, pre‐outbreak populations because the insects are difficult to sample in sufficient numbers. Using laboratory‐raised larvae installed in the field across a 1,000 km east–west gradient in Québec (Canada) over an 11‐yr period, we examined if parasitism and predation were likely to explain fluctuations in low‐density spruce budworm ( Choristoneura fumiferana ; SBW) populations. Parasitism rates by the two main larval parasitoid species, Elachertus cacoeciae and Tranosema rostrale , peaked during different years. This suggests that temporal fluctuations in overall parasitism were partly buffered by compensatory dynamics among parasitoid species. Still, spatial covariance analyses indicate that the residual interannual variation in parasitism rates was substantial and correlated over large distances (up to 700 km). On the other hand, interannual variation in predation rates was not spatially correlated. Piecewise structural equation models indicate that temporal variation in parasitism and predation does not influence temporal variation in wild SBW abundance. Spatially, however, SBWs installed in warmer locations tended to show higher parasitism rates, and these higher rates correlated with lower wild SBW population levels. Overall, the results indicate that large‐scale drops in parasitism occur and could potentially contribute to SBW population increases. However, during the period covered by this study, other factors such as direct effects of weather on SBW larval development or indirect effects through host tree physiology or phenology were more likely to explain large‐scale variation in wild SBW populations.

Osteomyelitis of the jaw: time to rethink the bone sampling strategy? - Kevin Bertrand; Brigitte Lamy; Marie De Boutray; Jacques Yachouh; Sophie Galmiche; Pierre Leprêtre; Nicolas Menjot de Champfleur; Jacques Reynes; Vincent Le Moing; David Morquin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Polar pesticide contamination of an urban and peri-urban tropical watershed affected by agricultural activities (Yaoundé, Center Region, Cameroon) - Perrine Branchet; Emmanuelle Cadot; Hélène Fenet; David Sebag; Benjamin Ngounou Ngatcha; Valérie Borrell-Estupina; Jules Remy Ndam Ngoupayou; Ives Kengne; Jean-Jacques Braun; Catherine Gonzalez (Environmental Science and Pollution Research, 2018)

More Thoughts on AG–SG Comparisons and SG Scale Factor Determinations - David Crossley; Marta Calvo; Severine Rosat; Jacques Hinderer (Pure and Applied Geophysics, 2018)

Removal of lead and cadmium from aqueous solutions by using 4-amino-3-hydroxynaphthalene sulfonic acid-doped polypyrrole films - Mohamed Lamine Sall; Abdou Karim Diagne Diaw; Diariatou Gningue-Sall; Alexandre Chevillot-Biraud; Nihal Oturan; Mehmet Ali Oturan; Chloé Fourdrin; David Huguenot; Jean-Jacques Aaron (Environmental Science and Pollution Research, 2018)

Climatic influences on the breeding biology of the agile frog (Rana dalmatina) - Magali Combes; David Pinaud; Christophe Barbraud; Jacques Trotignon; François Brischoux (The Science of Nature, 2018)

Chemical composition of some plantation wood species (Eucalyptus saligna, Cupressus lusitanica and Eucalyptus paniculata) and assessment of compatibility with plaster - David Vernon Chokouadeu Youmssi; Yves Didier Modtegue Bampel; Jacques Michel Njankouo; Jean-Bosco Saha Tchinda; Maurice Kor Ndikontar (Journal of the Indian Academy of Wood Science, 2017)

Topographic distribution of brain iron deposition and small cerebrovascular lesions in amyotrophic lateral sclerosis and in frontotemporal lobar degeneration: a post-mortem 7.0-tesla magnetic resonance imaging study with neuropathological correlates - Jacques De Reuck; David Devos; Caroline Moreau; Florent Auger; Nicolas Durieux; Vincent Deramecourt; Florence Pasquier; Claude-Alain Maurage; Charlotte Cordonnier; Didier Leys; Regis Bordet (Acta Neurologica Belgica, 2017)

Epistatic determinism of durum wheat resistance to the wheat spindle streak mosaic virus - Yan Holtz; Michel Bonnefoy; Véronique Viader; Morgane Ardisson; Nicolas O. Rode; Gérard Poux; Pierre Roumet; Véronique Marie-Jeanne; Vincent Ranwez; Sylvain Santoni; David Gouache; Jacques L. David (Theoretical and Applied Genetics, 2017)

Fighting Oxidative Stress: Increased Resistance of Male Rat Cerebellum at Weaning Induced by Low Omega 6/Omega 3 Ratio in a Protein-Deficient Diet - Ricielle Lopes Augusto; Alinny Rosendo Isaac; Ivanildo Inácio da Silva-Júnior; David Filipe de Santana; Diorginis José Soares Ferreira; Claudia Jacques Lagranha; Catarina Gonçalves-Pimentel; Marcelo Cairrão Araujo Rodrigues; Belmira Lara da Silveira Andrade-da-Costa (The Cerebellum, 2017)

The cyclochlorotine mycotoxin is produced by the nonribosomal peptide synthetase CctN in Talaromyces islandicus (‘ Penicillium islandicum ’) - Thomas Schafhauser; Norbert Kirchner; Andreas Kulik; Mieke M.E. Huijbers; Liane Flor; Thibault Caradec; David P. Fewer; Harald Gross; Philippe Jacques; Linda Jahn; Jouni Jokela; Valérie Leclère; et al. (Environmental Microbiology, 2016)
Summary Talaromyces islandicus (‘ Penicillium islandicum ’) is a widespread foodborne mold that produces numerous secondary metabolites, among them potent mycotoxins belonging to different chemical classes. A notable metabolite is the hepatotoxic and carcinogenic pentapeptide cyclochlorotine that contains the unusual amino acids β‐phenylalanine, 2‐aminobutyrate and 3,4‐dichloroproline. Although the chemical structure has been known for over five decades, nothing is known about the biosynthetic pathway of cyclochlorotine. Bioinformatic analysis of the recently sequenced genome of T. islandicus identified a wealth of gene clusters potentially coding for the synthesis of secondary metabolites. Here, we show by RNA interference‐mediated gene silencing that a nonribosomal peptide synthetase, CctN, is responsible for the synthesis of cyclochlorotine. Moreover, we identified novel cyclochlorotine chemical variants, whose production also depended on cctN expression. Surprisingly, the halogenase required for cyclochlorotine biosynthesis is not encoded in the cct cluster. Nonetheless, our findings enabled us to propose a detailed model for cyclochlorotine biosynthesis. In addition, comparative genomics revealed that cct ‐like clusters are present in all of the sequenced Talaromyces strains indicating a high prevalence of cyclochlorotine production ability.

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Functional and structural responses of soil N-cycling microbial communities to the herbicide mesotrione: a dose-effect microcosm approach - Olivier Crouzet; Franck Poly; Frédérique Bonnemoy; David Bru; Isabelle Batisson; Jacques Bohatier; Laurent Philippot; Clarisse Mallet (Environmental Science and Pollution Research, 2016)

A dynamic leaf gas‐exchange strategy is conserved in woody plants under changing ambient CO 2 : evidence from carbon isotope discrimination in paleo and CO 2 enrichment studies - Steven L. Voelker; J. Renée Brooks; Frederick C. Meinzer; Rebecca Anderson; Martin K.‐F. Bader; Giovanna Battipaglia; Katie M. Becklin; David Beerling; Didier Bert; Julio L. Betancourt; Todd E. Dawson; Jean‐Christophe Domec; et al. (Global Change Biology, 2016)
Rising atmospheric [CO 2 ], c a , is expected to affect stomatal regulation of leaf gas‐exchange of woody plants, thus influencing energy fluxes as well as carbon (C), water, and nutrient cycling of forests. Researchers have proposed various strategies for stomatal regulation of leaf gas‐exchange that include maintaining a constant leaf internal [CO 2 ], c i , a constant drawdown in CO 2 ( c a − c i ), and a constant c i / c a . These strategies can result in drastically different consequences for leaf gas‐exchange. The accuracy of Earth systems models depends in part on assumptions about generalizable patterns in leaf gas‐exchange responses to varying c a . The concept of optimal stomatal behavior, exemplified by woody plants shifting along a continuum of these strategies, provides a unifying framework for understanding leaf gas‐exchange responses to c a . To assess leaf gas‐exchange regulation strategies, we analyzed patterns in c i inferred from studies reporting C stable isotope ratios (δ 13 C) or photosynthetic discrimination (∆) in woody angiosperms and gymnosperms that grew across a range of c a spanning at least 100 ppm. Our results suggest that much of the c a ‐induced changes in c i / c a occurred across c a spanning 200 to 400 ppm. These patterns imply that c a − c i will eventually approach a constant level at high c a because assimilation rates will reach a maximum and stomatal conductance of each species should be constrained to some minimum level. These analyses are not consistent with canalization toward any single strategy, particularly maintaining a constant c i . Rather, the results are consistent with the existence of a broadly conserved pattern of stomatal optimization in woody angiosperms and gymnosperms. This results in trees being profligate water users at low c a , when additional water loss is small for each unit of C gain, and increasingly water‐conservative at high c a , when photosystems are saturated and water loss is large for each unit C gain.

The earliest securely dated hominin fossil in Italy and evidence of Acheulian occupation during glacial MIS 16 at Notarchirico (Venosa, Basilicata, Italy) - Alison Pereira; Sébastien Nomade; Pierre Voinchet; Jean Jacques Bahain; Christophe Falguères; Henri Garon; David Lefèvre; Jean Paul Raynal; Vincent Scao; Marcello Piperno (Journal of Quaternary Science, 2015)
The Early Middle Pleistocene site of Notarchirico (Basilicata, Italy) is a 7‐m‐thick fluvially emplaced sedimentary sequence rich in volcanic materials coming from the Monte Vulture stratovolcano. This site consists of 11 archaeological layers, some of which have yielded handaxes. One femur attributed to Homo heidelbergensis was also recovered from an upper level. We present in this study new 40 Ar/ 39 Ar and electron spin resonance ages that delimit the time of occupation of Notarchirico to between 670 ± 4 ka (14 ka) and 614 ± 4 ka (12 ka), therefore spanning mainly the glacial Marine Isotope Stage 16. Handaxes found in archaeosurface F are now securely dated to between 670 ± 4 ka (14 ka) and 661 ± 4 ka (14 ka) and prove that hominid populations living in southern Italy used Acheulian technology as early as the beginning of this stage. Futhermore, we placed the age of the human femur between 661 ± 4 ka (14 ka) and 614± 4 ka (12 ka). This fossil is therefore the oldest Middle Pleistocene human fossil discovered in Italy so far. Thanks to this new chronological framework, Notarchirico is now a key site in our understanding of the Early Acheulian culture in Western Europe.

Leaf form–climate relationships on the global stage: an ensemble of characters - Jian Yang; Robert A. Spicer; Teresa E. V. Spicer; Nan Crystal Arens; Frédéric M. B. Jacques; Tao Su; Elizabeth M. Kennedy; Alexei B. Herman; David C. Steart; Gaurav Srivastava; Rakesh C. Mehrotra; Paul J. Valdes; et al. (Global Ecology and Biogeography, 2015)
Aim Early in their evolution, angiosperms evolved a diversity of leaf form far greater than that of any other group of land plants. Some of this diversity evolved in response to varying climate. Our aim is to test the global relationship between leaf form in woody dicot angiosperms and the climate in which they live. Location We have compiled a data set describing leaf form (using 31 standardized categorical characters) from 378 natural or naturalized vegetation sites from around the world. Our data include sites from all continents except A ntarctica and encompass biomes from tropical to taiga, over a range of elevations from 0.5 m to over 3000 m. Methods We chose the C limate L eaf A nalysis M ultivariate P rogram sampling, scoring and analytical protocols to test the relationships between climate and leaf form, which is based on canonical correspondence analysis. Cluster analysis evaluates the role of historical factors in shaping the patterns, and pairwise Pearson correlations examine the relationships among leaf characters. Results Woody dicot leaf characters form a physiognomic spectrum that reflects local climate conditions. On a global scale, correlations between leaf form and climate are consistent, irrespective of climate regime, vegetation type or biogeographic history. Relationships with temperature variables are maintained even when leaf margin characters, regarded as being particularly well correlated with mean annual temperature, are removed. Main conclusions In natural woody dicot vegetation an integrated spectrum of leaf form has developed across multiple leaf character states and species. This spectrum appears more strongly influenced by prevailing climate than biogeographic history. The covariation of leaf traits across species suggests strong integration of leaf form. New methods of exploring structure in multidimensional physiognomic space enable better application of leaf form to palaeoclimate reconstruction.

The SARAL/AltiKa Altimetry Satellite Mission - Jacques Verron; Pierre Sengenes; Juliette Lambin; Jocelyne Noubel; Nathalie Steunou; Amandine Guillot; Nicolas Picot; Sophie Coutin-Faye; Rashmi Sharma; R. M. Gairola; D. V. A. Raghava Murthy; James G. Richman; et al. (Marine Geodesy, 2015)

Climate‐induced changes in host tree–insect phenology may drive ecological state‐shift in boreal forests - Deepa S. Pureswaran; Louis De Grandpré; David Paré; Anthony Taylor; Martin Barrette; Hubert Morin; Jacques Régnière; Daniel D. Kneeshaw (Ecology, 2015)
Climate change is altering insect disturbance regimes via temperature‐mediated phenological changes and trophic interactions among host trees, herbivorous insects, and their natural enemies in boreal forests. Range expansion and increase in outbreak severity of forest insects are occurring in Europe and North America. The degree to which northern forest ecosystems are resilient to novel disturbance regimes will have direct consequences for the provisioning of goods and services from these forests and for long‐term forest management planning. Among major ecological disturbance agents in the boreal forests of North America is a tortricid moth, the eastern spruce budworm, which defoliates fir ( Abies spp.) and spruce ( Picea spp.). Northern expansion of this defoliator in eastern North America and climate‐induced narrowing of the phenological mismatch between the insect and its secondary host, black spruce ( Picea mariana ), may permit greater defoliation and mortality in extensive northern black spruce forests. Although spruce budworm outbreak centers have appeared in the boreal black spruce zone historically, defoliation and mortality were minor. Potential increases in outbreak severity and tree mortality raise concerns about the future state of this northern ecosystem. Severe spruce budworm outbreaks could decrease stand productivity compared with their occurrence in more diverse, southern balsam fir forest landscapes that have coevolved with outbreaks. Furthermore, depending on the proportion of balsam fir and deciduous species present and fire recurrence, changes in regeneration patterns and in nutrient cycling could alter ecosystem dynamics and replace black spruce by more productive mixed‐wood forest, or by less productive ericaceous shrublands. Long‐term monitoring, manipulative experiments, and process modeling of climate‐induced phenological changes on herbivorous insect pests, their host tree species, and natural enemies in northern forests are therefore crucial to predicting species range shifts and assessing ecological and economic impacts.

Bioleaching of heavy metals from contaminated sediments by the Aspergillus niger strain SY1 - Xiangfeng Zeng; Shuhe Wei; Lina Sun; David A. Jacques; Jiaxi Tang; Meihua Lian; Zhanhua Ji; Jun Wang; Jianyu Zhu; Zixiang Xu (Journal of Soils and Sediments, 2015)

A Partition of Unity-Based Model for Crack Nucleation and Propagation in Porous Media, Including Orthotropic Materials - Ernst W. Remij; Joris J. C. Remmers; Francesco Pizzocolo; David M. J. Smeulders; Jacques M. Huyghe (Transport in Porous Media, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Transcriptome population genomics reveals severe bottleneck and domestication cost in the A frican rice ( O ryza glaberrima ) - Benoit Nabholz; Gautier Sarah; François Sabot; Manuel Ruiz; Hélène Adam; Sabine Nidelet; Alain Ghesquière; Sylvain Santoni; Jacques David; Sylvain Glémin (Molecular Ecology, 2014)
The African cultivated rice ( Oryza glaberrima ) was domesticated in West Africa 3000 years ago. Although less cultivated than the Asian rice ( O. sativa ), O. glaberrima landraces often display interesting adaptation to rustic environment (e.g. drought). Here, using RNA ‐seq technology, we were able to compare more than 12 000 transcripts between 9 O. glaberrima, 10 wild O. barthii and one O. meridionalis individuals. With a synonymous nucleotide diversity π s = 0.0006 per site, O. glaberrima appears as the least genetically diverse crop grass ever documented. Using approximate Bayesian computation, we estimated that O. glaberrima experienced a severe bottleneck during domestication. This demographic scenario almost fully accounts for the pattern of genetic diversity across O. glaberrima genome as we detected very few outliers regions where positive selection may have further impacted genetic diversity. Moreover, the large excess of derived nonsynonymous substitution that we detected suggests that the O. glaberrima population suffered from the ‘cost of domestication’. In addition, we used this genome‐scale data set to demonstrate that (i) O. barthii genetic diversity is positively correlated with recombination rate and negatively with gene density, (ii) expression level is negatively correlated with evolutionary constraint, and (iii) one region on chromosome 5 (position 4–6 Mb) exhibits a clear signature of introgression with a yet unidentified Oryza species. This work represents the first genome‐wide survey of the African rice genetic diversity and paves the way for further comparison between the African and the Asian rice, notably regarding the genetics underlying domestication traits.

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Modulation by the noble gas argon of the catalytic and thrombolytic efficiency of tissue plasminogen activator - Hélène N. David; Benoît Haelewyn; Jean-Jacques Risso; Jacques H. Abraini (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

GCM projections for the Pacific Decadal Oscillation under greenhouse forcing for the early 21st century - Suzan L. Lapp; Jeannine‐Marie St. Jacques; Elaine M. Barrow; David J. Sauchyn (International Journal of Climatology, 2012)
The climatology and hydrology of western North America display strong periodic cycles which are correlated with the low‐frequency Pacific Decadal Oscillation (PDO). The PDO's signature is seen throughout the entire North Pacific region, with related significant associations to hydrology and ecology in western North America and northeastern Asia. Therefore, the status of the PDO in a warmer world caused by anthropogenic climate change is of great interest. We developed early 21st‐century projections of the PDO, using data from archived runs of the most recent high‐resolution global climate models from the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment Report (Phase 3 of the Coupled Model Intercomparison Project). Because of the geographical adjacency and hypothesized interactions between the PDO and the El Niño‐Southern Oscillation (ENSO), and between the PDO and the North Atlantic Oscillation/Arctic Oscillation (NAO/AO), we also developed concurrent projections of ENSO and the NAO and examined their relationships with the projected PDO. For the B1, A1B and A2 Special Report on Emissions Scenarios (SRES) emission scenarios, the PDO projections for 2000–2050 showed a weak multi‐model mean shift towards more occurrences of the negative phase PDO, which becomes statistically significant for the time period 2000–2099. However, not all the models showed a consistent shift to negative PDO conditions. Copyright © 2011 Royal Meteorological Society

Elite durum wheat genetic map and recombination rate variation in a multiparental connected design - Laurence Vaissayre; Morgane Ardisson; Christiane Borries; Sylvain Santoni; Jacques David; Pierre Roumet (Euphytica, 2012)

Translational PK–PD modelling of molecular target modulation for the AMPA receptor positive allosteric modulator Org 26576 - Roberta Bursi; Gul Erdemli; Robert Campbell; Matthew M. Hutmacher; Thomas Kerbusch; David Spanswick; Ross Jeggo; Kari R. Nations; Peter Dogterom; Jacques Schipper; Mohammed Shahid (Psychopharmacology, 2011)

Using apparent soil electrical conductivity (ECa) to characterize vineyard soils of high clay content - José Ramon Rodríguez-Pérez; Richard E. Plant; Jean-Jacques Lambert; David R. Smart (Precision Agriculture, 2011)

Construction of a crop—wild hybrid population for broadening genetic diversity in cultivated sunflower and first evaluation of its combining ability: the concept of neodomestication - Hamidreza Nooryazdan; Hervé Serieys; Jacques David; Roberto Bacilieri; André J. Bervillé (Euphytica, 2011)

Community genetics. Its definition 2010 - Leo P. ten Kate; Lihadh Al-Gazali; Sonia Anand; Alan Bittles; Jean-Jacques Cassiman; Arnold Christianson; Martina C. Cornel; Hanan Hamamy; Helena Kääriäinen; Ulf Kristoffersson; David Marais; Victor B. Penchaszadeh; et al. (Journal of Community Genetics, 2010)

Role of human leukocyte antigen class I alleles in progressive multifocal leukoencephalopathy - Sarah Gheuens; Jacques Fellay; David B Goldstein; Igor J Koralnik (Journal of NeuroVirology, 2010)

Chronic administration of atypical antipsychotics improves behavioral and synaptic defects of STOP null mice - David Delotterie; Geoffrey Ruiz; Jacques Brocard; Annie Schweitzer; Corinne Roucard; Yann Roche; Marie-Françoise Suaud-Chagny; Karine Bressand; Annie Andrieux (Psychopharmacology, 2010)

Structure of wild annual sunflower (Helianthus annuus L.) accessions based on agro-morphological traits - Hamidreza Nooryazdan; Hervé Serieys; Roberto Baciliéri; Jacques David; André Bervillé (Genetic Resources and Crop Evolution, 2010)

Infection-associated FUT2 (Fucosyltransferase 2) genetic variation and impact on functionality assessed by in vivo studies - Lara M. Silva; Ana S. Carvalho; Patrice Guillon; Susana Seixas; Maria Azevedo; Raquel Almeida; Nathalie Ruvoën-Clouet; Celso A. Reis; Jacques Le Pendu; Jorge Rocha; Leonor David (Glycoconjugate Journal, 2010)

Widespread Gene Conversion of Alpha-2-Fucosyltransferase Genes in Mammals - Joana Abrantes; David Posada; Patrice Guillon; Pedro J. Esteves; Jacques Le Pendu (Journal of Molecular Evolution, 2009)

The relationship between monocarboxylate transporters 1 and 4 expression in skeletal muscle and endurance performance in athletes - David J. Bentley; Belle Roels; Claire Thomas; Robert Ives; Jacques Mercier; Grégoire Millet; David Cameron-Smith (European Journal of Applied Physiology, 2009)

Barium and molybdenum records in bivalve shells: Geochemical proxies for phytoplankton dynamics in coastal environments? - Julien ThÉbault; Laurent Chauvaud; StÉphane L'Helguen; Jacques Clavier; AurÉlie Barats; SÉverine Jacquet; Christophe PÉcheyran; David Amouroux (Limnology and Oceanography, 2009)
Barium : calcium and molybdenum : calcium ratios were investigated in shells of the tropical scallop Comptopallium radula . Three juvenile specimens were harvested alive in the southwest lagoon of New Caledonia after a 1‐yr hydrological survey. Calcite samples representing a few hours of biomineralization were laser‐ablated along the maximal growth axis and analyzed for Ba and Mo content with an inductively coupled plasma mass spectrometer. Absolute dates of shell precipitation assigned on the basis of periodic formation of shell growth patterns led to the accurate reconstruction of ontogenetic variations of elemental ratios with subweekly resolution. Interindividual variability of Ba : Ca and Mo: Ca time series was low, indicating an environmental control on the incorporation of these elements within shells. Both profiles were characterized by a background level punctuated by sharp peaks. The ingestion of diatoms enriched in Ba (adsorbed on iron oxyhydroxides associated with the frustules) is the most likely cause of the formation of Ba : Ca peaks. Some contribution of diatom‐associated barite is also possible. In every instance, Ba : Ca would possibly be a proxy for the timing and magnitude of diatom blooms. Among all the theories that could be advanced to explain the occurrence of Mo: Ca peaks, the most plausible appears to be the ingestion of phytoplankton cells grown on NO 3 − , and therefore containing high levels of Mo required for the activity of nitrate reductase. If this is so, then Mo: Ca could be a new proxy for nitrate uptake by phytoplankton in coastal ecosystems, helping to reconstruct the balance between new and regenerated production in paleoenvironments.

Estimation of model errors generated by atmospheric forcings for ocean data assimilation: experiments in a regional model of the Bay of Biscay - Gregoire Broquet; Pierre Brasseur; David Rozier; Jean-Michel Brankart; Jacques Verron (Ocean Dynamics, 2008)

Effects of intermittent hypoxic training on cycling performance in well-trained athletes - Belle Roels; David J. Bentley; Olivier Coste; Jacques Mercier; Grégoire P. Millet (European Journal of Applied Physiology, 2007)

Microsatellite segregation analysis and cytogenetic evidence for tetrasomic inheritance in the American yam Dioscorea trifida and a new basic chromosome number in the Dioscoreae - Mustapha Bousalem; Gemma Arnau; Isabelle Hochu; Richard Arnolin; Véronique Viader; Sylvain Santoni; Jacques David (Theoretical and Applied Genetics, 2006)

Evidence for a large‐scale population structure among accessions of Arabidopsis thaliana : possible causes and consequences for the distribution of linkage disequilibrium - MARIE‐FRANCE OSTROWSKI; JACQUES DAVID; SYLVAIN SANTONI; HEATHER MCKHANN; XAVIER REBOUD; VALERIE LE CORRE; CHRISTINE CAMILLERI; DOMINIQUE BRUNEL; DAVID BOUCHEZ; BENOIT FAURE; THOMAS BATAILLON (Molecular Ecology, 2006)
The existence of a large‐scale population structure was investigated in Arabidopsis thaliana by studying patterns of polymorphism in a set of 71 European accessions. We used sequence polymorphism surveyed in 10 fragments of ∼600 nucleotides and a set of nine microsatellite markers. Population structure was investigated using a model‐based inference framework. Among the accessions studied, the presence of four groups was inferred using genetic data, without using prior information on the geographical origin of the accessions. Significant genetic isolation by geographical distance was detected at the group level, together with a geographical gradient in allelic richness across groups. These results are discussed with respect to the previously proposed scenario of postglacial colonization of Europe from putative glacial refugia. Finally, the contribution of the inferred structure to linkage disequilibrium among 171 pairs of essentially unlinked markers was also investigated. Linkage disequilibrium analysis revealed that significant associations detected in the whole sample were mainly due to genetic differentiation among the inferred groups. We discuss the implication of this finding for future association studies in A . thaliana .

The TNFα receptor TNFRSF1A and genes encoding the amiloride-sensitive sodium channel ENaC as modulators in cystic fibrosis - Frauke Stanke; Tim Becker; Harry Cuppens; Vinod Kumar; Jean-Jacques Cassiman; Silke Jansen; Dragica Radojkovic; Benny Siebert; Jennifer Yarden; David W. Ussery; Thomas F. Wienker; Burkhard Tümmler (Human Genetics, 2006)

Partnering in Oncogenetic Research – The INHERIT BRCAs Experience: Opportunities and Challenges - Denise Avard; Peter Bridge; Lucie M. Bucci; Jocelyne Chiquette; Michel Dorval; Francine Durocher; Doug Easton; Béatrice Godard; David Goldgar; Bartha Maria Knoppers; Rachel Laframboise; Bernard Lespérance; et al. (Familial Cancer, 2006)

Molecular and genealogical characterization of the R1443X BRCA1 mutation in high-risk French-Canadian breast/ovarian cancer families - Hélène Vézina; Francine Durocher; Martine Dumont; Louis Houde; Csilla Szabo; Martine Tranchant; Jocelyne Chiquette; Marie Plante; Rachel Laframboise; Jean Lépine; Heli Nevanlinna; Dominique Stoppa-Lyonnet; et al. (Human Genetics, 2005)

Immunolocalization of vacuolar system-associated protein-60 (VASAP-60) - Sophie Brûlé; Robert Faure; Monique Doré; David W. Silversides; Jacques G. Lussier (Histochemistry and Cell Biology, 2003)

Fluid evolution in the Baia Mare epithermal gold/polymetallic district, Inner Carpathians, Romania - Luminita Grancea; Laurent Bailly; Jacques Leroy; David Banks; Eric Marcoux; Jean Milési; Michel Cuney; Anne André; Dumitru Istvan; Cécile Fabre (Mineralium Deposita, 2002)

Taste Sensitivity of Detritivorous Mosquito Larvae to Decomposed Leaf Litter - Jean-Philippe David; André Ferran; Jacques Gambier; Jean-Claude Meyran (Journal of Chemical Ecology, 2002)

Design and test of a generic cohort model of soil organic matter decomposition: the SOMKO model - Jacques Gignoux; Joanna House; David Hall; Dominique Masse; Hassan B. Nacro; Luc Abbadie (Global Ecology and Biogeography, 2001)
SOMKO is a new simulation model of soil organic matter (SOM) dynamics aimed at predicting long‐term and short‐term SOM dynamics based on a mechanistic approach focusing on microbes as the key agents of decomposition. SOM is partitioned into cohorts and chemical quality pools (classified by age and chemical composition), the microbial community processes are explicitly represented, and the C : N stoichiometric constraints are accounted for through a new mechanism of offer and demand. The analysis of model equations shows that: (1) SOM C : N cannot decrease below microbial C : N; and (2) the nitrogen limitation of decomposition depends on SOM C : N, microbial biomass and soil mineral nitrogen. First tests of the model show good qualitative behaviour for simulating the dynamics of short‐term litter‐bag type decomposition, long‐term SOM increase, pulsed mineral nitrogen production, the priming effect due to easily decomposable carbon addition, and the effects of vegetation clearance and climate change on SOM. Simulations are in good agreement with long‐term experimental data. SOMKO is an integrated component of the coupled soil–vegetation models within the ETEMA (European Terrestrial Ecosystem Modelling Activity) framework. Future extensions of this work include: (1) estimating microbial parameters from specific experiments; (2) spatial distribution of SOMKO in multistrata models; and (3) implementing nitrification/denitrification processes, phosphorus limitation and microfaunal activity.

Ly49A allelic variation and MHC class I specificity - Indira K. Mehta; Jian Wang; Jacques Roland; David H. Margulies; Wayne M. Yokoyama (Immunogenetics, 2001)

Promotion of sustainable capture fisheries and aquaculture in Asian reservoirs and lakes - Upali S. Amarasinghe; Annie Duncan; Jacques Moreau; Fritz Schiemer; David Simon; Jacobus Vijverberg (Hydrobiologia, 2001)

Feeding rates of the woodlouse Armadillidium vulgare on herb litters produced at two levels of atmospheric CO2 - Jean-François David; Nathalie Malet; Marie-Madeleine Coûteaux; Jacques Roy (Oecologia, 2001)

Influence of stream size on ammonium and suspended particulate nitrogen processing - Wilfred M. Wollheim; Bruce J. Peterson; Linda A. Deegan; John E. Hobbie; Beth Hooker; William B. Bowden; Kenneth J. Edwardson; David B. Arscott; Anne E. Hershey; Jacques Finlay (Limnology and Oceanography, 2001)
We used 15 NH 4 tracer additions to determine travel distances of ammonium (NH4 ) and suspended particulate organic nitrogen (SPON) in six streams ranging from second to fifth order located within a single watershed on the North Slope of Alaska. Based on the distribution of 15 N stored in stream bottom compartments (primary producers or grazers), we estimated NH 4 travel lengths. We used a two‐compartment model to estimate the travel length of SPON based on the distribution of source 15 N on the stream bottom and SPO 15 N in the water column. Both NH 4 and SPON travel lengths (S w and S p , respectively) increased with discharge primarily due to changes in depth and velocity. Variation in the vertical mass transfer coefficient ( v f ) of both NH 4 and SPON did occur among the streams but was not related to stream size and was relatively small compared to the change in physical characteristics. Thus, in the Kuparuk watershed, physical gradients outweighed biological or chemical changes as controls on NH 4 and SPON travel length. The one exception was the Kuparuk fertilized reach, where phosphorus fertilization greatly increased biological activity and NH 4 processing compared to unaltered streams. Longitudinal gradients in major biological driving variables such as litter inputs, debris dams, and shading are absent in the Arctic, perhaps explaining the relatively uniform NH 4 ‐ v f . Watersheds in other biomes may show differing degrees of physical versus biological/chemical controls. A conceptual model is presented for comparing the relative strength of these controls among different watersheds. Strong relationships between discharge and travel length should greatly aid development of watershed models of nutrient dynamics.

Time Variations In Gravity And Inferences On The Earth's Structure And Dynamics - Jacques Hinderer; David Crossley (Surveys in Geophysics, 2000)

Comparative responses to severe hypoxia and subsequent recovery in closely related amphipod populations (Gammarus minus) from cave and surface habitats - Frédéric Hervant; Jacques Mathieu; David C. Culver (Hydrobiologia, 1999)

The gene encoding T protein of the glycine decarboxylase complex involved in the mitochondrial step of the photorespiratory pathway in plants exhibits features of light-induced genes - Pierre Vauclare; David Macherel; Roland Douce; Jacques Bourguignon (Plant Molecular Biology, 1998)

Detection of heterozygous carriers of the ataxia-telangiectasia (ATM) gene by G 2 phase chromosomal radiosensitivity of peripheral blood lymphocytes - A. Tchirkov; Jacques-Olivier Bay; David Pernin; Yves-Jean Bignon; Pascale Rio; Maria Grancho; Fabrice Kwiatkowski; Michel Giollant; Paul Malet; Pierre Verrelle (Human Genetics, 1997)

Responses to pH of nine fishes and one shrimp native to New Zealand freshwaters - David W. West; Jacques A. T. Boubée; Rhys F. G. Barrier (New Zealand Journal of Marine and Freshwater Research, 1997)
The pH values preferred and avoided by adult stages of inanga (Galaxias maculatus) , common bully ( Gobiomorphus cotidianus) , common smelt (Retropinna retropinna) , and redfinned bully (G. huttoni) , were determined in a gradient tank (pH ranges of 3.2–11.2). Juvenile stages of inanga, common bully, shortjawed kokopu ( Galaxias postvectus) , koaro (G. brevipinnis) , banded kokopu ( G. fasciatus) , shortfinned (Anguilla australis) and longfinned ( A. dieffenbachii) elvers and glass eels, as well as freshwater shrimp (Paratya curvirostris) were also tested. Most species were found to have pH preferences and all except inanga avoided pH values of above c. 9.5. Adult fish showed stronger preferences than juveniles. An avoidance of pH values below 6.5 was apparent in most species except shortfinned elvers, koaro, and banded kokopu. Results indicate that the range of pH encountered in lowland streams are unlikely to have a major impact on the distribution of most New Zealand native freshwater fish.

Avoidance of suspended sediment by the juvenile migratory stage of six New Zealand native fish species - Jacques A. T. Boubée; Tracie L. Dean; David W. West; Rhys F. G. Barrier (New Zealand Journal of Marine and Freshwater Research, 1997)
The avoidance response of the migratory juvenile stage of six species of diadromous fish to different levels of suspended solid (SS) was determined in the laboratory using a two‐choice avoidance tank. Trials were mostly conducted with resuspended sediment from the outlet of Lake Waahi, New Zealand, but a series of tests was also conducted with kaolin for comparison. Banded kokopu (Galaxias fasciatus) was the most sensitive species, displaying a 50% avoidance response to kaolin and Waahi silt at 17 and 25 NTU, respectively. Koaro (Galaxias brevipinnis) and inanga (Galaxias maculatus) were found to be less sensitive than banded kokopu, with a 50% avoidance response to Waahi silt at 70 and 420 NTU, respectively. Shortfinned and longfinned elvers (Anguilla australis and/1, dieffenbachii) , and redfinned bullies (Gobiomorphus huttoni) showed no avoidance behaviour, even at the highest turbidities (1100 NTU) tested. Based on these laboratory results, and until field testing is undertaken, a limit of about 15 NTU in otherwise clear waterways should ensure that the upstream migration of some of the most common New Zealand native freshwater species will not be affected.

Refinement of the locus for autosomal dominant cerebellar ataxia type II to chromosome 3p21.1-14.1 - L. Krols; Jean-Jacques Martin; Gilles David; Nicole Van Regemorter; Ali Benomar; A. Lfgren; Giovanni Stevanin; Alexandra Drr; Alexis Brice; C. Van Broeckhoven (Human Genetics, 1997)

Studies of Mass-Movement Processes on Submarine Slopes - Lincoln Pratson; Homa Lee; Gary Parker; Marcelo Garcia; Bernard Coakley; David Mohrig; Jacques Locat; Ulisses Mello; Jeffrey Parsons; Sun-Uk Choi; Kenneth Isreal (Oceanography, 1996)